ABOUT LEXICO-SEMANTIC CHARACTERISTICS OF SOME PERSIAN COMPOUND WORDS IN “SADDI ISKANDARI” BY ALISHER NAVOI (Scientific journal of the Fergana State University, 2023)
This article deals with the Persian compound words used by the poet in the work of Alisher Navoi "Saddi Iskandari". The etymological features of the Persian compound words of the work, their lexical meanings, the fact that they are based on comments in Persian-Tajik dictionaries, comparison with comments given in other sources, scientific views on the lexical meanings of Persian words in the annotated dictionary of Navoi's works are given. The lexico-semantic meanings of the Persian compound words presented in the article are explained, and they are grouped according to the expression of the profession and action or state.